2015
DOI: 10.1242/dev.115642
|View full text |Cite
|
Sign up to set email alerts
|

UPF2, a nonsense-mediated mRNA decay factor, is required for prepubertal Sertoli cell development and male fertility by ensuring fidelity of the transcriptome

Abstract: Nonsense-mediated mRNA decay (NMD) represents a highly conserved RNA surveillance mechanism through which mRNA transcripts bearing premature termination codons (PTCs) are selectively degraded to maintain transcriptomic fidelity in the cell. Numerous in vitro studies have demonstrated the importance of the NMD pathway; however, evidence supporting its physiological necessity has only just started to emerge. Here, we report that ablation of Upf2, which encodes a core NMD factor, in murine embryonic Sertoli cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 65 publications
0
38
0
Order By: Relevance
“…Interestingly, one study showed the transcription of Amh in Leydig cells, questioning its selectivity to Sertoli cells (Ao, Erickson, & Stalvey, 1993). However, the purity of Leydig cell primary culture samples was not extensively evaluated in that study, and the results obtained could most likely be due to contamination by Sertoli cells (Bao et al, 2015;Garcia et al, 2014;Sridharan, Brehm, Bergmann, & Cooke, 2007). Another line of evidence for Sertoli cell-specificity of AMH comes from the extensive use of the Amh-cre deleter mouse line (Lécureuil, Fontaine, Crepieux, & Guillou, 2002) by investigators to specifically express or delete genes in Sertoli cells; no off-target effects are noted in Leydig cells, demonstrating the absence of AMH expression in Leydig cells (Garcia et al, 2014;Hurtado et al, 2018;Sridharan et al, 2007).…”
Section: Markers Used To Evaluate the Purity Of Rodent Sertoli Cellmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, one study showed the transcription of Amh in Leydig cells, questioning its selectivity to Sertoli cells (Ao, Erickson, & Stalvey, 1993). However, the purity of Leydig cell primary culture samples was not extensively evaluated in that study, and the results obtained could most likely be due to contamination by Sertoli cells (Bao et al, 2015;Garcia et al, 2014;Sridharan, Brehm, Bergmann, & Cooke, 2007). Another line of evidence for Sertoli cell-specificity of AMH comes from the extensive use of the Amh-cre deleter mouse line (Lécureuil, Fontaine, Crepieux, & Guillou, 2002) by investigators to specifically express or delete genes in Sertoli cells; no off-target effects are noted in Leydig cells, demonstrating the absence of AMH expression in Leydig cells (Garcia et al, 2014;Hurtado et al, 2018;Sridharan et al, 2007).…”
Section: Markers Used To Evaluate the Purity Of Rodent Sertoli Cellmentioning
confidence: 96%
“…The anti-Mullerian hormone (AMH), also known as Mullerian inhibiting substance, is an early Sertoli cell cytoplasmic protein with expression starting at embryonic day E12.5 that gradually decreases during Sertoli cell maturation(Bao, Tang, Yuan, Porse, & Yan, 2015; …”
mentioning
confidence: 99%
“…3D). In general, 1 1 transcripts containing a PTC are subjected to rapid degradation by NMD (29)(30)(31).…”
Section: Inefficiency Of Nmd Substantially Contributes To Accumulatiomentioning
confidence: 99%
“…Recently, an essential role for UPF2 has also been associated with male fertility. Conditional ablation of UPF2 in mouse embryonic Sertoli cells caused severe testicular atrophy, leading to sterility in adulthood …”
Section: Biological Functions Of Nmdmentioning
confidence: 99%
“…Conditional ablation of UPF2 in mouse embryonic Sertoli cells caused severe testicular atrophy, leading to sterility in adulthood. 146 SMG6 knockout mice also show early embryonic lethality, but using a conditional knockout strategy, SMG6 −/− mouse embryonic stem cells (ESCs) could be generated that proliferated normally and were morphologically indistinguishable from control ESCs. 147 Interestingly, such cultured SMG6 knockout ESCs were unable to undergo differentiation and retained high expression of pluripotency markers, and analysis of chimeric mice showed that the SMG6 −/− ESCs failed to differentiate into all three germ layers.…”
Section: Nmd Factors Are Required For Mammalian Developmentmentioning
confidence: 99%